2015
DOI: 10.1007/s00253-015-6402-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterial community involved in the bioflocculation process of wastewater organic matter in high-loaded MBRs

Abstract: High-loaded membrane bioreactors (HL-MBRs), i.e., bioreactors equipped with a membrane for biomass retention and operated at extremely short sludge and hydraulic retention times, can concentrate sewage organic matter to facilitate subsequent energy and chemical recovery from these organics. Bioflocculation, accomplished by microorganisms that produce extracellular polymers, is a very important mechanism in these reactors. Bacterial diversity of the sludge and supernatant fraction of HL-MBRs operated at very sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Almost all the biological processes have been explored in terms of biomass composition (bacteria, protozoa, metazoan, and fungi) and activity: conventional activated sludge, attached biomass, membrane reactors, and treating either municipal [27][28][29][30][31][32][33][34] or industrial wastewater [35][36][37][38][39]. Likewise, identification and quantification of microorganisms operating under different conditions (aerobic, anoxic, and anaerobic) have been reported [25,[40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all the biological processes have been explored in terms of biomass composition (bacteria, protozoa, metazoan, and fungi) and activity: conventional activated sludge, attached biomass, membrane reactors, and treating either municipal [27][28][29][30][31][32][33][34] or industrial wastewater [35][36][37][38][39]. Likewise, identification and quantification of microorganisms operating under different conditions (aerobic, anoxic, and anaerobic) have been reported [25,[40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature reports hundreds of applications of conventional and innovative biological tools, as well as examples of investigations based on ecological criteria [9,[20][21][22][23][24][25][26][27]. Almost all the biological processes have been explored in terms of biomass composition (bacteria, protozoa, metazoan, and fungi) and activity: conventional activated sludge, attached biomass, membrane reactors, and treating either municipal [27][28][29][30][31][32][33][34] or industrial wastewater [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Among the Chitinophagales, Ferruginibacter is among the top 10 bacterial predominant OTUs; represents 1.5% of the total reads within the third period of colonization of the SM_WWTP. Previous studies reported that Ferruginibacter are highly enriched in sludge and potentially associated with www.nature.com/scientificreports/ bio-flocculation and biofilms 53,54 consistently supporting their suggested role in floc formation. In a recent report, Saunders et al, analyzed the microbial communities in 13 Danish wastewater treatment plants in consecutive years and a single plant periodically over 6 years, using Illumina sequencing of 16S ribosomal RNA amplicons of the V4 region 4 .…”
Section: Exopolysaccharide Secretion and Flocs Formationmentioning
confidence: 61%
“…Consequently, the experiments of varying applied voltage demonstrated that large current was favorable for electron transfer for efficient NH 4 + production. However, studies have shown that different microorganisms have different tolerances to voltages, and high applied voltages make microorganisms more sensitive and inhibit growth, eventually becoming inactive 37 . Meanwhile, in order to avoid over‐occurrence of water splitting side‐reaction, the maximum voltage applied was only 1.5 V.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have shown that different microorganisms have different tolerances to voltages, and high applied voltages make microorganisms more sensitive and inhibit growth, eventually becoming inactive. 37 Meanwhile, in order to avoid overoccurrence of water splitting side-reaction, the maximum voltage applied was only 1.5 V.…”
Section: Resultsmentioning
confidence: 99%